1970
DOI: 10.2151/jmsj1965.48.5_417
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Falling Particles in Diabatic Atmospheres

Abstract: Diffusion of particles having an equal fall velocity which are released from a crosswind line source in diabatic atmospheres is studied. The wind profile and eddy diffusivity assumed in this investigation are those proposed by Yamamoto and Shimanuki as a revision of the KEYPS formula. The solution of the resulting diffusion equation is obtained numerically for various combinations of the source height, thermal stability and terminal velocity of the particles. In addition the deposition rate of particles on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The sedimentation of the material may be allowed by introducing a convection term in the mean steady equation that becomes [8,9]:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The sedimentation of the material may be allowed by introducing a convection term in the mean steady equation that becomes [8,9]:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The diffusion of particles is affected by their falling velocities in various ways when the sizes of particles are large enough. Yamamoto et al (1970) carried out numerical experiments of the diffusion of particles in the diabatic atmospheres, and they showed that the rate of deposition of particles on the ground depends on the falling velocity of particles. From those facts, it is expected that when the rain falls, the diffusion-sedimentation and washout processes occur simultaneously and therefore the size distri-bution of aerosols is changed by this combined process.…”
Section: Introductionmentioning
confidence: 99%